2013
DOI: 10.1007/s11746-013-2249-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Accelerated Storage on Microencapsulated Kenaf Seed Oil

Abstract: In order to improve the quality and protect against degradation, kenaf (Hibiscus cannabinus L.) seed oil was microencapsulated by using spray drying. The microencapsulated kenaf seed oil (MKSO) was then stored at 65 °C for 24 days, the changes of fatty acids and bioactive compounds were examined every six days. Bulk (unencapsulated) kenaf seed oil was used as a control and was compared to the MKSO. The fatty acids and phytosterols compositions were determined by using gas chromatography, while tocopherols and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 23 publications
6
62
1
2
Order By: Relevance
“…The n-6/n-3 ratio had an opposite behavior in DM (where it increased with the storage temperature) and in MM (where it decreased after storage, and this decrease was the same at 4 and 20 ºC). This contrast with other studies that have found no modification of the fatty acid composition of formulas with high content of PUFAs after 30 days of storage at 22 ºC (Zunin, Boggia, Turrini, & Leardi, 2015) or 24 days of storage at 65 ºC (Ng, Jessie, Tan, Long, & Nyam, 2013). However, differences in the composition of the oil and the capsules should be taken into account.…”
Section: Fatty Acid Composition Of the Total Oil Of Dm And MMcontrasting
confidence: 80%
See 1 more Smart Citation
“…The n-6/n-3 ratio had an opposite behavior in DM (where it increased with the storage temperature) and in MM (where it decreased after storage, and this decrease was the same at 4 and 20 ºC). This contrast with other studies that have found no modification of the fatty acid composition of formulas with high content of PUFAs after 30 days of storage at 22 ºC (Zunin, Boggia, Turrini, & Leardi, 2015) or 24 days of storage at 65 ºC (Ng, Jessie, Tan, Long, & Nyam, 2013). However, differences in the composition of the oil and the capsules should be taken into account.…”
Section: Fatty Acid Composition Of the Total Oil Of Dm And MMcontrasting
confidence: 80%
“…As a consequence, SFA/UFA and MUFA/PUFA ratios increased with the storage temperature. This decrease of PUFA could be a consequence of the ease breakage of double bond of these fatty acids, due to the high susceptibility of these fatty acids to oxidation (Ng, Jessie, Tan, Long, & Nyam, 2013). On the contrary, the level of MUFA remained unchanged in the case of MM and DM after a month of refrigeration storage with respect to initial time, and in the case of MM after a month of room storage with respect to initial time.…”
Section: Fatty Acid Composition Of the Total Oil Of Dm And MMmentioning
confidence: 92%
“…However, to overcome the toxicity and safety issues modern phyto-extraction techniques like sonication, soxhlet, supercritical carbon dioxide fluid extraction (SFE) etc. have been extensively utilized for extracting kenaf seed oil (Wang and Weller, 2006;Chan and Ismail, 2009;Foo et al, 2011;Mariod et al, 2011;Yazan et al, 2011;Ghafar et al, 2013;Ng et al, 2013). In recent time, soxhlet and SFE methods have extensively been used for extraction of kenaf seed oil with enriched fatty acids and antioxidants (Chan and Ismail, 2009;Nyam et al, 2010;Mariod et al, 2011;Ng et al, 2013).…”
Section: Extraction Of Kenaf and Roselle Seed Oilmentioning
confidence: 99%
“…The potential uses of kenaf seeds as a source of edible oil is often overlooked when considering kenaf as a fiber and feed crop (Coetzee et al, 2008). Kenaf seed oil can be considered nutritionally healthy because of the high concentration of polyunsaturated fatty acids and antioxidant activity (Nyam et al, 2009;Ng et al, 2013;Sara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%